2020
DOI: 10.3390/antibiotics9050241
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Bacteriophage Therapy for a Chronic MRSA Prosthetic Joint Infection

Abstract: This is a case of a 72 year old male with a chronic methicillin-resistant Staphylococcus aureus prosthetic joint infection. After the third intravenous dose of bacteriophage therapy, an unusual, reversible transaminitis prompted stoppage of bacteriophage therapy. Nevertheless, treatment was successful and the patient's severe chronic infection was eradicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 14 publications
2
85
0
3
Order By: Relevance
“…Critical appraisal highlighted various shortcomings in the quality of reporting but did not provide evidence of bias warranting exclusion (Supplementary File S3). A total of 17 eligible studies were identified for inclusion in this review [19,20,[23][24][25][26][27][32][33][34][35][36][37][38][39][40][41]. The data extracted from these studies is shown in Supplementary File S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical appraisal highlighted various shortcomings in the quality of reporting but did not provide evidence of bias warranting exclusion (Supplementary File S3). A total of 17 eligible studies were identified for inclusion in this review [19,20,[23][24][25][26][27][32][33][34][35][36][37][38][39][40][41]. The data extracted from these studies is shown in Supplementary File S2.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the nine articles that directly commented on safety or adverse effects reported no side-effects, with a seventh article highlighting that a patient's later myocardial infarction was not considered to be related to phage therapy [26]. Of the remaining two articles, Doub and colleagues suggested that their patient's pre-existing liver pathology explained their observation of non-life threatening reversible transaminitis in response to intravenous phage used at a titre of 2.7 × 10 9 plaque forming units (PFU)/mL [32]. This would be consistent with the absence of transaminitis among other patients treated with intravenous phage of a similar titre [27,36,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…While intravenous bacteriophage therapy has been used in the past with limited adverse events, recent compassionate use cases have shown two adverse events [ 38 , 39 ]. One occurred in the treatment of chronic pseudomonas left ventricular assist device (LVAD) infection in which no success occurred with low titers of intravenous bacteriophage therapy and subsequent bacteriophage therapy with high titers of 1 × 10 11 PFU induced fever, shortness of breath and wheezing [ 38 ]. These symptoms resolved with supportive medical care but continued with repeat dosing with the same titers.…”
Section: Parameters That Impact Treatment Protocolsmentioning
confidence: 99%
“…First, natural barriers such as cell layers and mucus can decrease accessibility of phages to sites of infection, thereby necessitating the administration of higher doses to achieve a favourable therapeutic effect. Second, phage clearance has been reported to occur rapidly; sometimes within just minutes to hours following parenteral administration in animal models and patients (14,(34)(35)(36)(37)(38)(39)(40). Phage clearance within the body is thought to be mediated by three main components: 1) Phagocytic cells (41), 2) The Mononuclear Phagocytic System (MPS;…”
Section: Introductionmentioning
confidence: 99%
“…During therapy, large quantities of phage monocultures or cocktails are administered to patients in order to maintain a killing titre to combat a bacterial infection. Once within the body, these phages can have very short half-lives and are actively removed or inactivated by the body (38)(39)(40)44). Following administration during phage therapy, epithelial and endothelial cell layers are amongst the first and most abundant phageeukaryote interactions.…”
Section: Introductionmentioning
confidence: 99%